Determinants of readiness for digital transformation in cooperatives: A case study in Thai Nguyen, Vietnam - Nguyen, Giang Thi; Ha, Trung Quang; Tran, Hong Le Thi Bich; Vu, Hien Thi; Ho, Xinh Luong; Bui, Tam Thanh Thi; Duong, Lam Xuan; Duong, An Hoai (Edelweiss Applied Science and Technology, 2025)
This study explores the determinants influencing cooperatives’ readiness for digital transformation in Thai Nguyen province, Vietnam, where empirical insights into this process remain limited. The purpose is to identify key internal and external factors that enhance or hinder readiness for digital change in the cooperative sector of a developing country. The research employed a mixed-methods design, combining online surveys and video interviews with 62 matured cooperatives between February and April 2025. Readiness was measured using a digital transformation index adapted from Vietnam’s updated Decision 2158 framework, and a multiple linear regression model—supported by LASSO regression—was applied to identify significant predictors. Findings reveal that over 80% of the surveyed cooperatives achieved advanced levels of digital readiness. Key factors positively associated with readiness include effective internal training, digital process integration, leadership understanding of digital trends, financial investment in innovation, robust internet connectivity, and supportive legal environments. The study concludes that both organizational capabilities and enabling environments are critical to fostering digital transformation. Practically, the findings provide targeted insights for policymakers and cooperative leaders to design strategies that promote digital maturity, resilience, and competitiveness in the cooperative sector. These insights are especially valuable for scaling digital initiatives in resource-constrained settings.